The role of L1 translation form in L2 compound processing: the case of native Czech speakers processing German noun-noun compounds - Kříž, Adam; Bordag, Denisa (Frontiers in Communication, 2023)
This study explores how Czech-German late bilinguals process German (L2) noun-noun compounds. Using a lexical decision task combined with translation constituent priming, we investigated two factors potentially influencing the L2 compound processing: a) the compound translation corresponds to one derived noun (e.g., Abendsternvečernice, 'evening star') or to an adjective + noun phrase (e.g., Weizenmehlpšeničná mouka, 'wheat flour'); and b) the compound translation entails translations of compound constituents (L1 translation of Abendstern, večernice, includes only first constituent, i.e. modifier, Abend = večer, 'evening'; L1 translation of Weizenmehl, pšeničná mouka, includes both constituents, Weizen = pšenice, 'wheat', Mehl = mouka, 'flour'). Two experiments were conducted; one focussing on head priming, the other on modifier priming. The results are in line with non-selective bilingual access and decomposition of L2 compounds. They reveal no influence of factor a), while b) affects processing.